2015
DOI: 10.1080/10255842.2015.1118467
|View full text |Cite
|
Sign up to set email alerts
|

Computational efficiency of numerical approximations of tangent moduli for finite element implementation of a fiber-reinforced hyperelastic material model

Abstract: In this study, we evaluated computational efficiency of finite element (FE) simulations when a numerical approximation method was used to obtain the tangent moduli. A fiber-reinforced hyperelastic material model for nearly incompressible soft tissues was implemented for 3D solid elements using both the approximation method and the closed-form analytical method, and validated by comparing the components of the tangent modulus tensor (also referred to as the material Jacobian) between the two methods. The comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The parameter h defines the angle between one of the mean local fiber direction and the circumferential axis of the local coordinate system. The anisotropic material model was implemented into ABAQUS with a user subroutine VUANISOHYPER [27][28][29].…”
Section: Methodsmentioning
confidence: 99%
“…The parameter h defines the angle between one of the mean local fiber direction and the circumferential axis of the local coordinate system. The anisotropic material model was implemented into ABAQUS with a user subroutine VUANISOHYPER [27][28][29].…”
Section: Methodsmentioning
confidence: 99%
“…The fiber orientation was defined by structural tensor, M i = m 0 i ⊗ m 0 i with m 0 1 = [ cosθ , sinθ , 0] and m 0 2 = [ cosθ , − sinθ ,0]. The anisotropic hyperelastic material model was implemented into Abaqus 6.14 (SIMULIA, Providence, RI) with a user sub-routine VUMAT 16, 33 . Local coordinate systems were defined for each leaflet to include fiber orientations for each region.…”
Section: Methodsmentioning
confidence: 99%
“…However, the lower CPU times are likely due to the somewhat random nature of low duration simulations that was found. Using a greater number of mesh refinements than previous studies, the normalized CPU times are shown to generally increase as the mesh is refined until it reaches a maximum before then decreasing with further refinements. However, the quadruple precision approximations all require more than twice the CPU time for all meshes.…”
Section: Finite Element Investigationmentioning
confidence: 66%
“…While the numerical approximations implemented here with optimal perturbation magnitude show quadratic convergence, it is known from the first implementation by Miehe that approximation methods have higher computation times. However, previous studies have shown that, with increased mesh refinement, the difference between analytical and approximate methods' solve times is decreased. This is due to the increased solution time required for the global matrix iterations in a more complex model, such that the computational effort of the stress and tangent components becomes less significant.…”
Section: Finite Element Investigationmentioning
confidence: 94%
See 1 more Smart Citation